Analysis of the Impact of the Trans-Sulawesi Railway Development on the Economy of South Sulawesi - Mabruri, M Hasan (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
Infrastructure development, particularly railway lines, plays a crucial role in accelerating economic growth, improving connectivity, and driving regional development. This study aims to analyze the impact of the Trans Sulawesi railway construction (Makassar–Parepare) on the economy of the community in South Sulawesi Province. The research uses a qualitative method with in-depth interviews with various stakeholders, including local communities, business actors, and government officials. The data obtained were analyzed using NVivo software to identify patterns and key themes arising from the interviews. The results show that the railway development has a positive impact on the local economy, such as improved accessibility, goods mobility, and the creation of new business opportunities. However, the main challenges faced are land acquisition and the need for improvements in supporting infrastructure. Overall, the railway project is expected to enhance regional economic competitiveness and accelerate the integration process between areas in Sulawesi.